2004
DOI: 10.1021/jp036235p
|View full text |Cite
|
Sign up to set email alerts
|

Thermosolvatochromism of Phenol Blue in Polar and Nonpolar Solvents

Abstract: The solvatochromic properties of phenol blue [N-(4-dimethylaminophenyl)-1,4-benzoquinoneimine] have been investigated in polar and nonpolar solvents using variable-temperature 1 H NMR and electronic absorption spectroscopy. In acetonitrile, chloroform, and cyclohexane, protons on the quinoneimine ring are inequivalent at all temperatures, while in methanol an exchange process increasingly broadens the signals from these protons as the temperature is raised. The temperature-dependent absorption spectrum of phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Phenol blue (PB), also known as N , N -dimethylindoaniline, N -(4-dimethylaminophenyl)-1,4-benzoquinoneimine, is a well-known nonfluorescent solvatochromic dye which has been widely studied by spectroscopic methods, such as resonance Raman scattering, time-resolved transient absorption (TRTA), , and NMR, , as well as theoretical simulations. PB is composed of an electron-donating (dimethylaniline) moiety connected to an accepting (benzoquinone monoimine) one by a π-conjugated bridge. Upon photoexcitation, charge transfer (CT) occurs from the donor to the acceptor moiety, and the contribution from the zwitterionic resonance structure becomes stronger than that from the covalent quinoneimine one in the first excited-singlet (S 1 ) state (Chart , top).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenol blue (PB), also known as N , N -dimethylindoaniline, N -(4-dimethylaminophenyl)-1,4-benzoquinoneimine, is a well-known nonfluorescent solvatochromic dye which has been widely studied by spectroscopic methods, such as resonance Raman scattering, time-resolved transient absorption (TRTA), , and NMR, , as well as theoretical simulations. PB is composed of an electron-donating (dimethylaniline) moiety connected to an accepting (benzoquinone monoimine) one by a π-conjugated bridge. Upon photoexcitation, charge transfer (CT) occurs from the donor to the acceptor moiety, and the contribution from the zwitterionic resonance structure becomes stronger than that from the covalent quinoneimine one in the first excited-singlet (S 1 ) state (Chart , top).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that because of the inhomogeneous distribution of the solvation environment, the narrow band of the excitation laser selects the individual “solvation state” at each wavelength. Meanwhile, the visible absorption band of PB is reported to exhibit not only solvatochromism but also thermochromism in MeOH solution . By increasing the temperature, the maximum absorbance decreases, and the absorption band slightly shifts to shorter wavelengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FTIR spectrum ( Fig. 22 The signals at 7.42 and 7.31 ppm might correspond to the benzenoid protons of the 1,4-benzoquinoneimine ring, 23 while the peaks centered at 6.18 and 5.60 ppm should be related to the benzenoid protons of substituted 1,4-benzoquinone. The sharp band at 1444 cm À1 is attributed to the skeletal CQC stretching vibration of the substituted aromatic ring, and the signal observed at 1413 cm À1 could be assigned to symmetric stretching of the phenazine heterocyclic ring.…”
Section: Resultsmentioning
confidence: 99%
“…21 Concretely, the benzenoid aromatic protons could be identified by these signals centered at 7.47, 7.26 and 7.00 ppm, indicative of the ending benzene rings in these oligomers. 22 The signals at 7.42 and 7.31 ppm might correspond to the benzenoid protons of the 1,4-benzoquinoneimine ring, 23 while the peaks centered at 6.18 and 5.60 ppm should be related to the benzenoid protons of substituted 1,4-benzoquinone. 24 These results indicate the presence of 1,4-benzoquinoneimine and 1,4-benzoquinone segments in the aniline oligomers.…”
Section: Chemical Structures and Morphologymentioning
confidence: 99%